2013
DOI: 10.1111/jvp.12058
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of melamine and cyanuric acid in kidney of catfish Ictalurus punctatus and trout Oncorhynchus mykiss

Abstract: A risk assessment conducted in 2007 identified significant knowledge gaps about tissue residues of melamine and related triazine analogs such as cyanuric acid in animals that had eaten contaminated food. The USFDA subsequently designed studies to determine residue levels in muscle, serum, and kidneys of catfish and trout given a single gavage dose of 20 mg/kg body weight (BW) of melamine, cyanuric acid, or 20 mg/kg BW of both compounds simultaneously. Renal triazines were determined by LC-MS/MS at postdose day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Food for human and animal consumption has been adulterated with melamine and cyanuric acid for economically motived reasons because these compounds can increase apparent protein content [19,29]. The purpose of this PT was to evaluate Vet-LIRN laboratories' ability to detect and quantify melamine and cyanuric acid in fish, for human consumption, at concentrations close to the level of concern (2.5 mg/kg) [30].…”
Section: Melamine Ptmentioning
confidence: 99%
“…Food for human and animal consumption has been adulterated with melamine and cyanuric acid for economically motived reasons because these compounds can increase apparent protein content [19,29]. The purpose of this PT was to evaluate Vet-LIRN laboratories' ability to detect and quantify melamine and cyanuric acid in fish, for human consumption, at concentrations close to the level of concern (2.5 mg/kg) [30].…”
Section: Melamine Ptmentioning
confidence: 99%
“…The crystals or stones in the urinary tract by exposure to MEL was reported to mainly consist of complexes of MEL with uric acid or cyanuric acid (CYA) [ 9 , 10 ]. Animal studies reported a strong synergistic effect on urolithiasis in the event of co-exposure to both MEL and CYA [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%